Calculated futures : theology, ethics, and economics - Long, D. Stephen, 1960- (Book collections on Project MUSE., 2007)
Calculated Futures examines the ethical and theological underpinnings of the free-market economy, investigating not only the morality of corporations and exchange rates, but also how the politics of economics shape people as moral agents. It does this less by insisting on the unfavorable effects of capitalism, and more by drawing on theological virtues, Christian doctrines, and liturgical practices to discover what they might show us about economic exchanges. Calculated Futures seeks a way forward by engaging economics as a social scientific discipline without subordinating theology to it.